Crystal orientation effect on fretting fatigue induced geometrically necessary dislocation distribution in Ni-based single-crystal superalloys. (15th October 2019) - Han, Qi-Nan; Rui, Shao-Shi; Qiu, Wenhui; Ma, Xianfeng; Su, Yue; Cui, Haitao; Zhang, Hongjian; Shi, Huiji
Abstract: The effect of crystal orientation on fretting fatigue induced crack initiation and dislocation distribution is studied by in-situ SEM observation and electron back-scattered diffraction (EBSD) in this paper. Cracks and slip lines are observed in the fretting contact area of Ni-based single-crystal (NBSX) superalloys. The in-situ SEM observation captures different crack and slip line behaviors under different crystal orientations. The EBSD analysis results show obvious misorientation and orientation deviation in the fretting contact area. For both crystal orientations, the geometrically necessary dislocation (GND) density distributions in the contact area are obtained by using Hough-based EBSD methods. The peak position of grain reference orientation deviation (GROD) and GND density matches with the fretting fatigue crack formation position. EBSD analysis shows that the dislocation density distribution on each slip system is closely related to the crack initiation direction. The direction of slip system with the maximum dislocation density agrees with the crack initiation direction obtained by in-situ observation. Graphical abstract: Image 1 Highlights: In-situ observation of fretting fatigue shows different crack and slip line behaviors of different crystal orientations. EBSD results show obvious misorientation in the fretting contact area. The peak position of GND density matches with the fretting fatigue crack formation position. The direction of slip system with the maximum dislocation density agrees with the crack direction.